Cuckoo optimised 2DOF controllers for stabilising the frequency changes in restructured power system with wind-hydro units - Peddakapu, K.; M. R., Mohamed; M. H., Sulaiman; Srinivasarao, P.; Kishore, D. J. K.; P. K., Leung (Taylor & Francis, 2021)
This paper introduces an innovative approach for automatic generation control (AGC) of multi-area diverse sources of the interconnected systems under a restructured scenario. In this work, proportional-integral (PI), proportional-integral derivative (PID), and 2-degree of freedom PID (2-DOF-PID) controllers are proposed to stabilise the variations in the system parameters at distinct loading conditions. Different types of metaheuristic optimisation methods like teaching–learning-based optimisation (TLBO) and cuckoo search algorithms are suggested to acquire the optimal gain values of the proposed controllers. To alleviate the frequency and inter-area power line deviations, the cuckoo tuned 2-DOF-PID controller has rendered better dynamic performances in terms of overshoot, settling time, and undershoot over other control approaches. Further, the robustness of the system has been ascertained while varying the loading circumstances and system specifications up to ±25% from their prescribed values which helped to exhibit the ability of the proposed method